Audit Delay in Manufacturing Firms: How Profitability, Liquidity, and Governance Drive Sustainable Economic Growth (SDG 8) and Industrial Innovation (SDG 9) - Muhamad Rubiul Yatim; Indra Satria; Ismiriati Nasip; Riana Fajrin (Goodwood Publishing, 2026)
Purpose: This study examines the effects of profitability, liquidity, and audit committee composition on audit delay in manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, with company size as a moderating variable. This study explores how governance and financial health impact the timeliness of financial reporting, aligning with Sustainable Development Goals (SDG 8) (economic growth). Research Methodology: Using Moderate Regression Analysis (MRA) and a purposive sample of 33 data points from 11 firms, the study employs five models (R-squared from 0.234 to 0.992) to assess the effects of the variables on audit completion delay. Results: Profitability, liquidity, and audit committee composition significantly affect audit delays. Company size moderates the effects of profitability (p<0.001) and audit committee composition (p<0.001) but not liquidity (p=0.096). These findings emphasize the role of organizational size in shaping transparent financial reporting, thereby supporting SDG 12 (responsible consumption). Conclusions: This study highlights the importance of considering company size when assessing the impact of profitability, liquidity, and audit committee composition on audit delay, contributing to more effective governance and financial transparency. These findings align with SDG 9 (Industry and Infrastructure) and SDG 10 (Reducing Inequalities). Limitations: The study is limited by its small sample size of 11 firms, which may not fully represent the broader industry. Contributions: This study is one of the first to examine the moderating effect of company size on audit delay in Indonesia’s manufacturing sector, advancing SDG 9.